Good governance and transparency - Vilone, Laura (2020)
The notion of “good governance” implies the special place given to the State. Such a model is defined by the effectiveness of certain guarantees such as the independence of the judiciary, the correct and fair management of expenditure but also administrative transparency. Indeed, the latter depends on the sincerity of those involved in public action, on the one hand, and the constant dialogue between the public authorities and the public, on the other hand. The purpose of this intervention is to demonstrate that the realisation of the model of “good governance” is based, above all, on the existence of an administration that fully understands the requirements of administrative transparency. The two pillars of “good governance” would thus be the foundations of the principle of transparency: communication with citizens and their participation in the process of the decision-making process.